Peranan PT JPLM pada Skema Relasi Kopi dalam upaya Peningkatan Ekspor Kopi di Bandung Selatan - Evalina Darlin; Inna Hanarti; Nurdin Nurdin (Neolectura, 2022)
Based on data on the development of Indonesian coffee exports to several countries in 2015-2019, it can be seen that the development of coffee exports tends to decline. For this reason, PT Java Preanger Lestari Mandiri (PT JPLM) takes a role in overcoming the decline in coffee exports, especially in South Bandung Regency. The scope of this study includes the potential and form of relationships, as well as assistance to Preanger Arabica coffee farmers. The research was focused in the area of South Bandung Regency, West Java. Qualitative research methods with data collection techniques are triangulation and inductive data analysis. In the first stage, researchers conducted research on the export value of Indonesian coffee for the past five years. Second, researching the form of the coffee relationship scheme carried out by PT JPLM. Third, researching the form of marketing support and developing coffee sales cooperation with potential buyers at home and abroad. This study aims to analyze the form of coffee relationship schemes carried out by PT JPLM to coffee farmers. Through this research, the first one will be exposed clearly and in detail about the potential for coffee exports that have not been optimized, the second will be the results of a clear analysis of how the form of coffee relations between PT JPLM and coffee farmers and the third will be known about the impact of coffee relations on coffee farmers.